Studies on Monstereae (Araceae) of Peninsular Malaysia IV: the enigmatic Rhaphidophora corneri refound after 75 years - Zulhazman Hamzah; Peter C. Boyce; Sofiman Othman (2012)
Rhaphidophora corneri P.C.Boyce, a highly distinctive but hitherto poorly known species described from fragmentary material collected by E.J.H. Corner late in 1935 from Kemaman (Terengganu state in Peninsular Malaysia) has recently been refound in neighbouring Kelantan. A much-expanded species description is provided, along with new information pertaining to its ecology. A reinterpretation of possible relationships with other Rhaphidophora species is offered in light of these novel data. Photographs depicting newly observed vegetative morphology are provided.